Ultrasound-guided ablation for hepatocellular carcinoma: time for a reappraisal?. Issue 2 (February 2014) - Cabibbo, Giuseppe; Antonucci, Michela; Sacco, Rodolfo; Sciarrino, Elio
<x xml:space="preserve">Abstract</x> Ultrasound-guided techniques play a key role in the clinical management of hepatocellular carcinoma. Among these, percutaneous ethanol injection (PEI) was the first technique to be proposed for the treatment of nodular-type hepatocellular carcinoma: the role of PEI was first discussed during the European Association for the Study of the Liver conference held in Barcelona in 2000, 15 years ago. Since then, other techniques have been introduced and radiofrequency ablation now represents the most widely used percutaneous technique. PEI and radiofrequency ablation are widely used in clinical practice. However, only scant progresses in the application of these techniques have been performed over the past 15 years, and percutaneous approaches are often only marginally discussed and studied. Here, we discuss the most relevant clinical issues regarding PEI and radiofrequency ablation that have emerged in the past years.